Підвищення конкурентоспроможності підприємства в сучасних умовах - Верютіна, Марія Михайлівна; Семенчук, Тетяна Юріївна; Ткачова, Надія Петрівна (НТУ "ХПІ", 2017)
Конкурентоспроможність підприємства – це можливість ефективно розпоряджатися власними й позиковими ресурсами в умовах конкурентного ринку. Розглянуто поняття конкурентоспроможність та її форми. Розглянуто види конкурентних стратегій. Зазначено ризики існуючих конкурентних стратегій. Запропоновано ефективну стратегію для підвищення конкурентоспроможності. Для перевірки ефективності стратегій було детально їх розглянуто. Підвищення конкурентоспроможності було розглянуто на прикладі магазину стоматологічного обладнання та матеріалів.

Competitiveness of an enterprise is the ability to effectively manage its own and borrowed resources in a competitive market. The concepts of competitiveness and its forms are considered. The types of competitive strategies are considered. The risks of existing competitive strategies are indicated. An effective strategy for improving competitiveness was proposed. To test the effectiveness of strategies, they were considered in detail. The increase in competitiveness was examined using the example of a store of dental equipment and materials. For today the store can offer a large selection of dental materials and equipment, service and advice on equipping the dentist office from scratch.
Increase of competitiveness of the enterprise in modern conditions
Keywords: конкурентоспроможність підприємства; конкурентні стратегії; ризики конкурентних стратегій; enterprise competitiveness; competitive strategies; risks of competitive strategies